Evaluation of dosing and safety outcomes of low-dose prophylactic warfarin in children after cardiothoracic surgery. (29th May 2020) - Harkin, Maura; Shaddix, Brittany Powers; Neely, Stephen B; Peek, Leigh A; Stephens, Katy; Barker, Philip; McMullan, Lauren; Gormley, Andrew; Johnson, Peter N
Abstract: Purpose: Prophylactic warfarin with an International Normalized Ratio (INR) goal of 1.5 to 2.0 is one antithrombotic therapy utilized in children after cardiothoracic surgery (CTS); published sources suggest a dose of 0.1 mg/kg per day to achieve this goal. However, few studies have evaluated dosing in this population. The purpose of this study was to evaluate dosing and safety outcomes in children receiving warfarin after CTS. Methods: A descriptive, retrospective review was conducted to evaluate warfarin dosing and INR outcomes in patients 18 years of age or younger who underwent CTS and received prophylactic warfarin with an INR goal of 1.5 to 2.0 from January 2014 through December 2018. The primary objective was to determine the median initial warfarin dose. Secondary objectives included identifying the percentage of documented INR values that were outside the therapeutic range, the percentage of patients with therapeutic INRs at discharge, and the 30-day readmission rate. Results: Twenty-six patients were included in the review. The median initial warfarin dosage was 0.07 mg/kg/d (interquartile range [IQR], 0.05-0.10 mg/kg/d). Of the total of 177 INR values collected during the entire study period, 67 (37.9%) were therapeutic, 64 (36.2%) were subtherapeutic, and 46 (26.0%) were supratherapeutic. Eighteen patients (69.2%) had at least 1 supratherapeutic INR at any point during the study period, most frequently on days 2 through 4 of therapy. At discharge, 11 patients (42.3%) had therapeutic INRs. Four patients (15.4%) were readmitted within 30 days, with bleeding documented in 2 patients during their readmission. Conclusion: The majority of patients received an initial warfarin dose less than that specified in published recommendations but still had a supratherapeutic INR at least once during the study period. When initiating warfarin after CTS, a dosage of <0.1 mg/kg per day and frequent monitoring may be needed to achieve an INR goal of 1.5 to 2.0.